Social sciences in crisis: on the proposed elimination of the discussion section. - Schoenegger, Philipp; Pils, Raimund (Synthese, 2023)
The social sciences are facing numerous crises including those related to replication, theory, and applicability. We highlight that these crises imply epistemic malfunctions and affect science communication negatively. Several potential solutions have already been proposed, ranging from statistical improvements to changes in norms of scientific conduct. In this paper, we propose a structural solution: the elimination of the discussion section from social science research papers. We point out that discussion sections allow for an inappropriate narrativization of research that disguises actual results and enables the misstatement of true limitations. We go on to claim that removing this section and outsourcing it to other publications provides several epistemic advantages such as a division of academic labour, adversarial modes of progress, and a better alignment of the personal aims of scientists with the aims of science. After responding to several objections, we conclude that the potential benefits of moving away from the traditional model of academic papers outweigh the costs and have the potential to play a part in addressing the crises in the social sciences alongside other reforms. As such, we take our paper as proffering a further potential solution that should be applied complimentarily with other reform movements such as Open Science and hope that our paper can start a debate on this or similar proposals.